2021
DOI: 10.3390/ijerph18179248
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid Insomnia and Obstructive Sleep Apnea (COMISA): Current Concepts of Patient Management

Abstract: Obstructive sleep apnea (OSA) and insomnia are the two most common sleep disorders among the general population, and they may often coexist in patients with sleep-disordered breathing (SDB). The higher prevalence of insomnia symptoms in patients with OSA (40–60%) compared to that observed in the general population has thus led researchers to identify a new disorder named comorbid insomnia and OSA (COMISA), whose true burden has been so far largely underestimated. The combined treatment of COMISA patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 93 publications
(134 reference statements)
0
36
0
Order By: Relevance
“…One latest clinical study also found that trazodone reduces AHI and increases the awakening threshold of obstructive sleep apnea after ischemic stroke 18 . It might be another advantage of Trazodone in clinical application as the higher prevalency of insomnia symptoms in patients with OSA (40–60%) compared to that observed in the general population 42 . Further, it is worth discussing whether trazodone is more suitable for comorbid insomnia and OSA patients to improve their sleep quality or to improve their compliance with continuous positive airway pressure (CPAP) treatment.…”
Section: Discussionmentioning
confidence: 99%
“…One latest clinical study also found that trazodone reduces AHI and increases the awakening threshold of obstructive sleep apnea after ischemic stroke 18 . It might be another advantage of Trazodone in clinical application as the higher prevalency of insomnia symptoms in patients with OSA (40–60%) compared to that observed in the general population 42 . Further, it is worth discussing whether trazodone is more suitable for comorbid insomnia and OSA patients to improve their sleep quality or to improve their compliance with continuous positive airway pressure (CPAP) treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, although the implementation of an adequate combined treatment of comorbid insomnia disorder could open new perspectives to allow a better cardiovascular outcome in apnoeic individuals [ 54 ], it seems essential to take into account the specific features of this particular subpopulation for the choice of this combined treatment in order to avoid the establishment of treatments with a negative impact for the management of OSAS [ 55 ]. Indeed, since most pharmacological treatments for comorbid insomnia disorder may have a deleterious effect on respiratory parameters in apnoeic individuals, cognitive–behavioural therapy for insomnia combined with optimal treatment of OSAS (lifestyle changes plus continuous positive airway pressure therapy/mandibular advancement devices/surgery) seems to be the best therapeutic option for apnoeic individuals with comorbid insomnia disorder [ 56 , 57 ]. Finally, alongside this combined treatment of comorbid insomnia disorder in apnoeic individuals, it is essential to establish adequate therapeutic strategies for conventional cardiovascular risk factors in order to allow integrated cardiovascular management in this particular subpopulation [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The OSA MSB subgroup was less numerous, which could result in a relatively more narrow IQR of AC and AD. Explanation of these wide ranges remains beyond the scope of this study; however, it is now widely discussed that the comorbidity of different sleep disorders is a relatively common phenomenon [ 53 , 54 , 55 ]. Participants in this study were not checked for comorbid PLM disorder or insomnia, but it was previously reported that such disorders are likely to contribute to increased MA in sleep [ 29 , 56 ].…”
Section: Discussionmentioning
confidence: 99%